Mechanism for G2 phase-specific nuclear export of the kinetochore protein CENP-F. Issue 15 (3rd August 2017) - Loftus, Kyle M.; Cui, Heying; Coutavas, Elias; King, David S.; Ceravolo, Amanda; Pereiras, Dylan; Solmaz, Sozanne R.
ABSTRACT: Centromere protein F (CENP-F) is a component of the kinetochore and a regulator of cell cycle progression. CENP-F recruits the dynein transport machinery and orchestrates several cell cycle-specific transport events, including transport of the nucleus, mitochondria and chromosomes. A key regulatory step for several of these functions is likely the G2 phase-specific export of CENP-F from the nucleus to the cytosol, where the cytoplasmic dynein transport machinery resides; however, the molecular mechanism of this process is elusive. Here, we have identified 3 phosphorylation sites within the bipartite classical nuclear localization signal (cNLS) of CENP-F. These sites are specific for cyclin-dependent kinase 1 (Cdk1), which is active in G2 phase. Phosphomimetic mutations of these residues strongly diminish the interaction of the CENP-F cNLS with its nuclear transport receptor karyopherin α. These mutations also diminish nuclear localization of the CENP-F cNLS in cells. Notably, the cNLS is phosphorylated in the −1 position, which is important to orient the adjacent major motif for binding into its pocket on karyopherin α. We propose that localization of CENP-F is regulated by a cNLS, and a nuclear export pathway, resulting in nuclear localization during most of interphase. In G2 phase, the cNLS is weakened by phosphorylation through Cdk1, likely resulting in nuclear export of CENP-F via the still active nuclear export pathway. Once CENP-F resides in the cytosol, it can engage in pathways that are important for cell cycle progression, kinetochore assembly and the faithful segregation of chromosomes into daughter cells.